If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-(x+3)=2x-1
We move all terms to the left:
2-(x+3)-(2x-1)=0
We get rid of parentheses
-x-2x-3+1+2=0
We add all the numbers together, and all the variables
-3x=0
x=0/-3
x=0
| -6-9(1+2.5n)=18.5 | | 6t^2-3t-1=0 | | 76/24x-9/24=41/24 | | 25x-6x+15x-4=20x+10 | | s+2.8=8.6 | | -15x(^2)+10x+200=0 | | 7^(x-5)=1 | | 2/3/7/8=n/1/8 | | 7^x-5=1 | | (0.3)^x+1=0.7^x | | x-34=20 | | 700+80+n=780+n= | | (3-2x)²=5 | | 9x^2-12x+4=64 | | 3(2-x)=(6-5x)+2 | | 9x+16=12+6x+13 | | 6(v-8)+8=-82 | | -9x+5=6x-4 | | -7(5-2p)=-91 | | 3.6=3c;c=12 | | 5k+4=29 | | 23=n+2+2n | | 30-x-10=0 | | 21-h=15/h=6 | | -1/2m+2=-1 | | x(x+11)=1452 | | 5a-8=10 | | x(x+1)=1452 | | 9y+12=11y-12 | | x(x+1)=-1452 | | x(x+1)=-1320 | | 2. x =2x-3x=2 |